Study of FoxP3+ CD4+ CD25+ in systemic lupus erythematosus and rheumatoid arthritis - Farag Khalil; Mohamed Nabil Rafat; Abdelwahab Lotfy; Mahmoud H Hemida; Marwan Sayed; Mamdouh Attia (SpringerOpen, 2018)
Background Systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) as autoimmune diseases arise owing to failure of immunological self-tolerance. One of the mechanisms employed to control these potentially damaging cells are regulatory T cells (Tregs). The importance of Tregs is underscored by the overwhelming inflammation and autoimmunity that result from their absence. Forkhead box p3 (FoxP3) is an important regulator of Treg function, and the expression of FoxP3 correlates with the expression of other Treg-associated markers such as CD25 and CTLA-4. Aim To investigate the frequency of FoxP3+ CD4+ CD25+high cells (Tregs) in peripheral blood from patients with SLE and those with RA. Patients and methods A total of 25 patients with SLE (15 patients with active SLE and 10 patients with inactive SLE), 25 patients with RA (15 patients with active RA and 10 patients with inactive RA), and 10 age-matched and sex-matched healthy controls were enrolled in the study. Patients underwent clinical and laboratory assessment. The frequency of Tregs was determined by flow cytometry. Results The distribution of FoxP3+ CD4+ CD25+high cells (Tregs) revealed a highly significant decrease in the frequency of Treg in patients with SLE compared with healthy controls. Moreover, patients with active SLE showed significantly lower Tregs percent when compared with inactive group. Moreover, the distribution of FoxP3+ CD4+ CD25+high cells (Tregs) revealed a high significantly decrease in the frequency of Treg in patients with RA compared with healthy controls. Conclusion CD4+ CD25+ FoxP3 Tregs (as a percent of total CD4 cells) were significantly lower in patients with SLE and those with RA when compared with healthy controls.